2018
DOI: 10.1080/0886022x.2018.1455594
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 is a strong predictor of insulin resistance among chronic kidney disease patients

Abstract: Insulin resistance (IR) is very common among chronic kidney disease (CKD) patients. Disturbance in mineral and bone metabolism (MBD) seems to play a role in the pathogenesis of insulin resistance. Fibroblast growth factor-23 (FGF23) is evolving as the most important link between MBD and many pathologic sequences of CKD. The aim was to evaluate IR in pre-dialysis CKD patients looking for a possible association to mineral metabolism among CKD patients. A total of 100 stage 3–5 CKD patients were selected beside 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The association between FGF23 and insulin deficiency (type 1 diabetes) and resistance (type 2 diabetes) is, however, complex. In many cross‐sectional studies, FGF23 is positively correlated with obesity, diabetes or HOMA‐IR, a parameter indicating insulin resistance . According to other studies, FGF23 is inversely associated with insulin resistance .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 97%
“…The association between FGF23 and insulin deficiency (type 1 diabetes) and resistance (type 2 diabetes) is, however, complex. In many cross‐sectional studies, FGF23 is positively correlated with obesity, diabetes or HOMA‐IR, a parameter indicating insulin resistance . According to other studies, FGF23 is inversely associated with insulin resistance .…”
Section: Homeostatic Regulation Of Fgf23mentioning
confidence: 97%
“…A lot of evidence has revealed that 1,25(OH)2D3 is closely related to the occurrence of autoimmune diseases ( 6 , 7 ). Vitamin D can inhibit inflammation and immune reaction, promote synthesis and secretion of insulin and increase insulin sensitivity ( 8 ). A review has revealed that vitamin D deficiency has a potential influence on T1DM incidence, complications and progression ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, FGF23 was not correlated with parameters of carbohydrate metabolism and body composition. In a previous study by Fayed et al (2018), FGF23 was found to be an important predictor of IR in CKD patients. In contrast, Hanks et al (2015) found that FGF23 was not correlated with IR in a group of patients with CKD.…”
Section: Discussionmentioning
confidence: 79%